Model of Community-Led Total Sanitation Pillar One: Open Defecation Free in Sagulung Subdistrict, Batam City - Tita Widya Arindayu; R. Azizah; Arif Sumantri; Lovetta Yatta Juanah; Ahmadi Ahmadi; Salsabila Al Firdausi; Juliana Jalaludin; Shaharuddin Mohd Sham (Universitas Airlangga, 2021)
Introduction: Community-Led Total Sanitation (CLTS) is an effort by the government to improve public health. The main focus of pillar one is to stop open defecation. Sagulung Subdistrict has verified and non-verified ODF villages in their working area. This paper aims to create a CLTS model based on the pillar of one ODF in the Sagulung Subdistrict. Methods: This research used a mixed-method that combining qualitative and quantitative approaches. An amount of 90 families were chosen as respondents using a simple random sampling technique. Besides that, three programmers and five implementers from the government also became respondents. Data were analysed with a Chi-Square test and descriptive analysis. Results and Discussion: This research showed that ODF declaration and local policies were the aspects that had not been fulfilled to the maximum on CLTS pillar one in the Sugulung Subdistrict Government. Sungai Lekop Primary Health Care had not fully fulfilled three aspects: the concept, planning, and targets (advocated and local policies). As a Non-ODF village, Sungai Langkai primary health care did not fulfil the concept, planning, and target (certificate of the training program, advocated, declaration of ODF and local policies). Conclusion: Variables that have not been fulfilled optimally can be arranged as a recommendation model to successful ODF in Sagulung Subdistrict.